Reinforcing Male Dominance and Power through Moving Canvas: A Content Analysis of Truck Literature - Gurung, Dil Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Truck literature is calligraphy writing on the back, side, or front of trucks and public buses. They contain messages on social awareness, love, and political satire. While such inscriptions often serve to spread social awareness, many contain humorous, romantic, or gender-biased messages that implicitly reflect and reinforce the dominance of a single stratum of people, male. To understand how truck literature is reflecting and reinforcing masculinity and male dominance, 37 vehicles were selected on an opportunistic sampling basis. The truck literatures were collected at three different highway locations in Nepal. The collected truck literature were clustered into two themes: other (general truck literature such as awareness, love, and political satire-related messages) and gender biased messages. The study found that more than half of the sample vehicles had messages about the dominance of masculinity over femininity. These examples of truck literature often employ humor to normalize and perpetuate male dominance over women. Knowingly or unknowingly, the messages in those moving canvases were hilarious; notwithstanding, these works of literature are meant to reinforce traditional gender roles and sexuality and to stabilize the dominance of masculinity over femininity.